RITUAL INTERACTION IN THE SONEYAN MASK PUPPET - Wuryaningrum, Any; Sumaryanto, Totok; Hartono, Hartono (Universitas Negeri Semarang, 2017)
The preservation of traditional arts depends on the artists and their supporters. The Soneyan Mask Puppet artistic life is still showing its existence as a medium of expression for fulfilling the needs of the arts. Until now The Soneyan Mask Puppet has undergone five generations. In the beginning, the show performed by the puppeteers of gedhog puppet and purwo puppet. The shows were accompanied by the slendro type of Javanese traditional music, in the form of Pamijen music. Before the show begins, rituals were held. The rituals were part of the Mask Puppet show. Therefore, the activity of the Soneyan Mask Puppet can not be separated from the rituals. Based on the description, the primary purpose of this study is to assess the ritual interaction in The Soneyan Mask Puppet. This is a qualitative research with an approach to social, cultural and performing arts. The data were drawn from the techniques of observation, interviews, and documentary study. The data analysis procedures followed Miles and Huberman (1984) data reduction, data presentation, and conclusion. Among the results of this research is that the process of ritual interaction in the Soneyan Mask Puppet is in the form of symbolic interaction contained in ritual offerings before the show begins. The symbolic interaction is found in a ritual that is highly expressed in the offerings consisting of ambeng, incense, straw, combs of banana, chicken eggs, chili, shrimp paste, upa, coconut shoot, brown sugar, dried fish, mboreh flower, jugs, cigarettes, teeter , money (two combs bananas, eggs, chili, rice, coconut, brown sugar, dried fish, mboreh flowers, jugs, cigarettes, combs, money).